STRUCTURAL CONTROL RELATED WITH ALTERATION AND HIGH SULFIDATION EPITHERMAL AU-AG-CU MINERALIZATION SYSTEM AT PIT B EAST AND B WEST, TUJUH BUKIT MINE, BANYUWANGI, EAST JAVA - Aji Dermawan, Ilham
Tujuh Bukit generally consists of Late Oligocene Middle Miocene volcanic and volcaniclastic Batuampar Formation. After tectonomagmatism took place at Pliocene, this stratigraphic unit altered and became a host rock for Pliocene economic mineralization. The research area located in open pit mining at Pit B East and B West. Both pits have an extensive area of ± 700 x 500 m2, projected on ± 9045100 9045600 mN and ± 174400 175100 mE UTM WGS 1984 zone 50S coordinate system. This research discusses about structural control as the main role of alteration characteristics and Au-Ag-Cu high sulfidation epithermal mineralization system forming in open pit mining at Pit B East and B West, Tujuh Bukit mine. Final purposes are to reveal the orientation and main structural system that control Au- Ag-Cu mineralization forming, especially medium to very high-grade mineralization. Mapping in open pit wall bench are conducted with detail observation in alteration characteristics, mineralization identification, and structural geology. Then rock samples are brought to microscopic identification to find out the alteration, minerals paragenetic from cross-cutting/overprinting relationship, and ore minerals composition. Analytical Spectral Devices (ASD) instrument used to find out the name of specific mineral from particular minerals group, especially clay mineral. Atomic Absorption Spectroscopy (AAS) geochemical test are used to determine Au-Ag-Cu grade in ppm unit. Secondary data usage given by company are conducted with the same methodology. Based on lithostratigraphic analysis, the research area consists of volcanic breccia unit which compared to Late Oligocene Middle Miocene Batuampar Formation. Polymictic breccia consist of pyroclastic matrix and igneous, tuff-lapilli, sedimentary rocks, and locally charcoal fragments. This stratigraphic unit became a host rock for mineralization after tectonomagmatism activity took place at Pliocene. The unit was deformed and hydrothermal fluids trough deformation pathway to deposited an ore mineral and altered the rocks. Main developed structural are Pliocene strike-slip system, relatively NW-SE and N-S orientation, with NNW-SSE principal stress following pure shear model. There also relatively NW-SE normal fault and ENE-WSW thrust fault. All of these faults in regional scale are NNW-SSE compressive tectonic compensation within one tectonic period. Strike-slip system resulting normal fault and ridge zones within releasing stepover, releasing bend, and restraining bend structural geometry. Strike-slip faults in Pit B East and B West are the smallest strike-slip system within Tujuh Bukit regional scale. Developed structural geology representing recent tectonic of Java. Five alteration units concluded after data integration from field, drilling, and ASD scanning, there are quartz, quartz-alunite, quartz-kaolinite, kaolinitemontmorillonite- chlorite, and kaolinite-montmorillonite alteration unit. Rocks alteration generally have medium to intense alteration intensity, locally found total alteration. According to alteration terminology based on the mineral assemblages, all the units are silicification, advanced argillic, and intermediate argillic alteration. Overprinting relationship found out from petrographic analysis revealed that all alteration units occurred in two phases. First phase was formed in acidic pH environment, and the second phase was formed in acidic to neutral pH environment due to meteoric water influence has play a role. Au-Ag-Cu mineralization classification divided into five class of grade, respectively, that are very low, low, medium, high, and very high grade. Based on field and mineragraphic observation, there found ore minerals such as pyrite, chalcopyrite, covellite, bornite, tetrahedrite, azurite, malachite, hematite, and goethite. All these minerals generally found associated within silicification alteration, such as quartz, quartz-alunite, and quartz-kaolinite alteration unit. Development of medium to very high-grade mineralization within these alteration unit generally took place in normal fault zones caused by strike-slip system on the releasing bend and releasing stepover geometry, and normal fault which parallel to the principal stress on regional scale. The development of structure, alteration, and mineralization controlled by subduction between Indo-Australia and Eurasian Plate at Pliocene, which occurred on southern of Java with relatively NNW-SSE orientation. The tectonic deformed pre-Pliocene rocks and caused magmatism activity. Economic mineralizationbearing magmatism has an activity duration up to 3.59 m.y. since 5.29 Ma.